USO DEL ENSILADO BIOLÓGICO DE PESCADO EN LA ALIMENTACIÓN DE CUYES MEJORADOS - Mattos C., Jessika (2003)
The study evaluated the effect of the fish silage on feed rations for Guinea Pig (Cavia porcellus). Eighty guinea pigs of the Peruvian line (1/2 blood) , weaned at 14 ± 3 days of age, were used. The treatments consisted of different levels of fish silage: 0 (D0), 10 (D10), 20 (D20) and 30% (D30). The study lasted 10 weeks and was divided in three stages: 0-42, 42-70 and 0-70 days. Body weight gain and food intake was higher in D10, D20 and D30 as compared to DO (p<0.05), whereas no differences were found between D10, D20 and D30. In all stages, food conversion was higher in D20 and D30. The carcass performance was better in D30 and the economic benefit was better in D20. The organoleptic trial suggested that meat flavor and smell were affected on D20. It was concluded that the use of fish silage in the rations improved the productive performance of the guinea pig, where 20% content was the most appropiate based on organoleptic and economic terms.